Comparative life cycle assessment study on environmental impact of oil production from micro-algae and terrestrial oilseed crops. (September 2017) - Jez, S.; Spinelli, D.; Fierro, A.; Dibenedetto, A.; Aresta, M.; Busi, E.; Basosi, R.
Highlights: A comparative LCA of microalgae oil and terrestrial oilseeds crops was carried out. Microalgae oil has the greatest impact due to the electricity consumption. Three scenarios for micro-algae oil with renewable source was investigated. Photovoltaics compared to biogas shows the best environmental performances. Co-products valorization might reduce the impact of algae oil. Abstract: In this study the LCA methodology is applied in order to satisfy two goals: i) to evaluate the hot spots in site-specific production chain of biodiesel from terrestrial and micro-algae feedstock; ii) to compare quantitatively, utilizing primary data, the impacts of the first generation in respect to the third generation bio-fuels. Results show that micro-algae are neither competitive yet with traditional oil crops nor with fossil fuel. The use of renewable technologies as photovoltaics and biogas self production might increase the competitiveness of micro-algae oil. Further investigations are however necessary to optimize their production chain and to increase the added value of co-products.